Taxonomic re-examination of Japanese brook lampreys of the genus Lethenteron with descriptions of two new species, Lethenteron satoi sp. nov. and Lethenteron hattai sp. nov., and re-description of Lethenteron mitsukurii - Sakai, Harumi; Iwata, Akihisa; Watanabe, Katsutoshi; Goto, Akira (Ichthyological research, 2025)
A taxonomic re-examination of Japanese brook lampreys (genus Lethenteron) from morphological and genetic perspectives revealed the existence of five species, Lethenteron satoi sp. nov., Lethenteron hattai sp. nov. (formerly recognized as Lethenteron sp. S), Lethenteron mitsukurii (Hatta 1901) (formerly Lethenteron sp. N), Lethenteron reissneri (Dybowski 1869) [sometimes confused with Lethenteron kessleri (Anikin 1905)], and Lethenteron camtschaticum (Tilesius 1811). Lethenteron satoi sp. nov., currently known only from Hokkaido, Japan, differs from congeners by the combination of the following characters: body yellowish brown, gular region unpigmented, caudal fin and apex of second dorsal fin lacking black pigment, caudal fin round, neuromast clusters absent ventrally between adjacent branchial pores, transverse lingual lamina triangular without median tooth, teeth present as round protuberances on supraoral and infraoral laminae, trunk myomeres (TM) 55–61, myomeres below first dorsal fin base (FDFM) 12–15, myomeres under second dorsal fin base (SDFM) 33–35, and myomeres from first dorsal fin base end to cloaca (FDFCM) 8–13. Lethenteron hattai sp. nov., distributed from Honshu, Shikoku and Kyushu Islands, Japan, and southern Korean Peninsula, is diagnosed by the combination of the following characters: body yellowish brown, gular region unpigmented, caudal fin and apex of second dorsal fin lacking black pigment, caudal fin rhomboidal or spade shaped, neuromast clusters present ventrally between adjacent branchial pores, transverse lingual lamina with 1–5 median teeth, teeth on supraoral and infraoral laminae present, being obtuse and triangular, and low rounded mounds, respectively, TM 53–60, FDFM 15–19, SDFM 34–39, and FDFCM 4–9. Lethenteron mitsukurii, distributed from Hokkaido to Honshu Islands, Japan, is redescribed; it differs from congeners by the combination of the following characters: body yellowish brown, gular region unpigmented, caudal fin and apex of second dorsal fin lacking black pigment, caudal fin rhomboidal or spade shaped, neuromast clusters absent ventrally between adjacent branchial pores, transverse lingual lamina with 1 median tooth, teeth on supraoral and infraoral laminae present, being obtuse and triangular, and low rounded mounds, respectively, TM 59–65, FDFM 15–20, SDFM 34–39, and FDFCM 8–13. Morphological keys for Japanese species of Lethenteron are provided.